PROTECTION OF EMPLOYEES IN OUR LEGAL SYSTEM WITH REFERENCE TO AGROCOMPLEX - Vukićević, Slavoljub J. (Economics of Agriculture, 2006)
This study deals with the always present question of the safety and protection of employees which is especially popular in the conditions of transitional changes that our society is going through and in accordance with it our economic system, in which agrocomplex has a significant place. There is an emphasis on general conditions in which employees work and on normative solutions of our legal system which follow the norms contained in the law of the EU and in comparative legal system as well.